Three‐Dimensional Echocardiography‐Based Prediction of Posterior Leaflet Resection. Issue 10 (11th August 2014) - Rim, Yonghoon; Choi, Ahnryul; Laing, Susan T.; McPherson, David D.; Kim, Hyunggun
<x xml:space="preserve">Abstract</x> Clinical long‐term outcomes have shown that partial leaflet resection followed by ring annuloplasty is a reliable and reproducible surgical repair technique for treatment of mitral valve (MV) leaflet prolapse. We report a 61‐year‐old male for three‐dimensional transesophageal echocardiography (3DTEE)‐based virtual posterior leaflet resection and ring annuloplasty. Severe mitral regurgitation was found and computational evaluation demonstrated substantial leaflet malcoaptation and high stress concentration. Following virtual resection and ring annuloplasty, posterior leaflet prolapse markedly decreased, sufficient leaflet coaptation was restored, and high stress concentration disappeared. Virtual MV repair strategies using 3DTEE have the potential to help optimize MV repair.